Optimal control strategies for the premium policy of an insurance firm with jump diffusion assets and stochastic interest rate - Dalila Guerdouh; Nabil Khelfallah; Josep Vives (Journal of Risk and Financial Management, 2022)
In this paper, we present a stochastic optimal control model to optimize an insurance firm problem in the case where its cash-balance process is assumed to be described by a stochastic differential equation driven by Teugels martingales. Noticing that the insurance firm is able to control its cash-balance dynamics by regulating the underlying premium rate, the aim of the policy maker is to select an appropriate premium in order to minimize the total deviation of the state process to some pre-set target level. As a part of stochastic maximum principle approach, a verification theorem is used to fulfill this achievement.
Keywords: 330; forward-backward stochastic differential equations; teugels martingales; lévy processes; optimal premium policies